Ox of masks: memory and immaterial patrimony - Santos Silva, Silvia Sueli (2021)
The goal of this paper is to reflect over the identities and cultural transformations of the contemporary street masquerades as of the contribution of the recognition process of such festivities as immaterial goods, having as analysis object the Ox play known as Ox ofmasks - São Caetano de Odivelas (PA). The Ox of Masks, or Odivelas Ox, is classified as a street masquerade. Similarly, other festivities that have the figure of the dancing ox as the protagonist of the scene present today significant cultural transformations in its visuality and scenic representation, at the same time as they fight for recognition as immaterial patrimony that is identifying and representative of their culture. It discusses the implications of the patrimonialization for the local communities, in which the festivities enforce the bonds between ancestral traditions and the new generations, comprehending in them their aggregating and transformative power in the social and cultural relationships.